Leaf anatomical variation in Desmos Lour. and Dasymaschalon (Hook. f. & Thomson) Dalla Torre & Harms species (Annonaceae) - Isna Arofatun Nikmah; Rugayah Rugayah; Tatik Chikmawati (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Nikmah IA, Rugayah R, Chikmawati T. 2020. Leaf anatomical variation in Desmos Lour. and Dasymaschalon (Hook. f. & Thomson) Dalla Torre & Harms species (Annonaceae). Biodiversitas 21: 3317-3330. The relationships between Desmos and Dasymaschalon are debated for along time. Those two genera have high morphological similarities, especially in their generative character (moniliform monocarps). Therefore, sterile specimens of Desmos are difficult to be distinguished from Dasymaschalon. Leaf anatomy in paradermal section of 20 taxa (12 species of Desmos, eight species of Dasymaschalon) have been carried out. The data were used to support the interspecific and intergeneric delimitation of Desmos and Dasymaschalon. Desmos and Dasymaschalon are two distinct genera mainly distinguished based on the anticlinal wall undulation of epidermal cells and supported by variation of the crystal type, and size. The anticlinal wall undulation of Desmos is almost straight to slightly wavy, and never sinuous, meanwhile, Dasymaschalon varies from almost straight to deeply sinusoid. The crystals of Desmos consist of rhombohedric, druse type A, and druse type B crystals, whereas Dasymaschalon has prism, druse type A, druse type B, and drue type C crystals.